Effet de l’engrais « CETEP » sur le rendement des cultures de haricot nain dans le Sud-Kivu - Innocent Karhagomba Balagizi; Adrien Chifizi; Espoir Mukengere Bagula; Jean Mihigo Cizungu; Trésor Mirindi Adhama; Pascal Mulungula Masilya; Mwapu Isumbisho (VertigO, 2013)
This chapter describes the results of a comparative trial of yields of bushbean (variety M’sole) cultivated on plots amended with organic manure “CETEP” and plots covered with conventional manure “NPK”. The CETEP manure is made from rural innovations in Kamisimbi whilst NPK is under commercialization. From the trials, farming results shows positive effects of CETEP manure on soil fertility. Looking to combination NPK+ Organic Matter, CETEP + Organic Matters the CETEP proved to be more efficient of all in term of the quantitative farming yields with a regards on environmental and economic positive impacts. Therefore, the CETEP manure should be popularized in the way of promoting small scale-farming with low external input.